China's image in the Spanish press during the COVID-19 pandemic - Zhang, Cen (Círculo de Lingüística Aplicada a la Comunicación, 2024)
This study analyzes the representation of China in the Spanish press during the COVID-19 pandemic, utilizing an analytical framework comprised of appraisal theory, transitivity system, and corpus linguistics. Our research is based on a specialized corpus consisting of 271 articles extracted from the Spanish newspapers El País, El Mundo, La Vanguardia, and ABC. Various analytical techniques, including keywords, collocations, and concordances, are applied to identify patterns and trends in the representation of China. The findings reveal that the Spanish newspapers have conveyed a multifaceted portrayal of China, employing various linguistic resources, both explicit and implicit, to express their attitudinal stance. The evaluative prosody towards China is variable, with instances of both positive and negative assessments. On one hand, the effectiveness of the anti-COVID measures implemented by China and the country’s capacity in managing the crisis are positively appraised. On the other hand, the Chinese healthcare system is criticized, certain measures are deemed draconian, and an image of ambitious and arrogant China is constructed occasionally. This study provides significant insights into how the Spanish media represents China during the COVID-19 pandemic and contributes to an enhanced understanding of the importance and feasibility of studying images from a discursive approach.
Keywords: COVID-19; China's image; media representation; evaluation